Body composition changes of hooded seal (Cystophora cristata) pups during extreme lactation - Guerrero, Maria Alizia (UiT Norges arktiske universitet, 2018)
Among phocids, the hooded seal has the most extreme lactation period. It lasts, for most pups, four days, making it also the shortest lactation period of any mammal. During the lactation period, there is a high energy transfer, which affects and changes the body of the pup in preparation for the following post-weaning fast period. With regard to the decline of the West Ice population, the main purpose of this study was to examine the changes in the body composition and energy deposition of the West Ice pups during the lactation period, as well as the maternal strategy of the West Ice female hooded seals. In addition, energy deposition during pregnancy and during the lactation period over the last 10 years was investigated. From 2007 to 2018, as part of a series of student expeditions, newborn (n= 14) pups and weaned seals (n= 17) were captured in the West Ice. All pups (n= 31) were submitted to a detailed dissection for measurement of body composition. Energy deposition was assayed by chemical analysis for the last two weaned pups. Body composition of newborn pups and weaned pups were significantly different. Newborn pups had a blubber content of 30.7 ± 2.9 %, while weaned pups had a body composition that was 46.6 ± 1.7 % blubber. During lactation, muscle mass increased by 23%, while blubber content increased by 63 %. Comparison of maternal strategies of the West Ice and Northwest Atlantic stock presented a significant difference, West Ice hooded seals appear to be born and weaned with greater deposits of blubber than hooded seals of the Northwest Atlantic population. Additionally, it seems that there has been a decline in the energy deposited by the female hooded seals into the weaned pups.